New Approaches to Radiation Protection - Rosen, Eliot M.; Day, Regina; Singh, Vijay K. (Frontiers in Oncology, 2015)
Radioprotectors are compounds that protect against radiation injury when given prior to radiation exposure. Mitigators can protect against radiation injury when given after exposure but before symptoms appear. Radioprotectors and mitigators can potentially improve the outcomes of radiotherapy for cancer treatment by allowing higher doses of radiation and/or reduced damage to normal tissues. Such compounds can also potentially counteract the effects of accidental exposure to radiation or deliberate exposure (e.g., nuclear reactor meltdown, dirty bomb, or nuclear bomb explosion); hence they are called radiation countermeasures. Here, we will review the general principles of radiation injury and protection and describe selected examples of radioprotectors/mitigators ranging from small-molecules to proteins to cell-based treatments. We will emphasize agents that are in more advanced stages of development.